Decreased BDNF Release in Cortical Neurons of a Knock-in Mouse Model of Huntington's Disease. Issue 1 (December 2018) - Yu, Chenglong; Li, Chun; Chen, Sidong; Yoo, Hanna; Qin, Xianan; Park, Hyokeun
Abstract Huntington's disease (HD) is a dominantly inherited neurodegenerative disease caused by an increase in CAG repeats in the Huntingtin gene (HTT ). The striatum is one of the most vulnerable brain regions in HD, and altered delivery of BDNF to the striatum is believed to underlie this high vulnerability. However, the delivery of BDNF to the striatum in HD remains poorly understood. Here, we used real-time imaging to visualize release of BDNF from cortical neurons cultured alone or co-cultured with striatal neurons. BDNF release was significantly decreased in the cortical neurons of zQ175 mice (a knock-in model of HD), and total internal reflection fluorescence microscopy revealed several release patterns of single BDNF-containing vesicles, with distinct kinetics and prevalence, in co-cultured cortical HD neurons. Notably, a smaller proportion of single BDNF-containing vesicles underwent full release in HD neurons than in wild-type neurons. This decreased release of BDNF in cortical neurons might lead to decreased BDNF levels in the striatum because the striatum receives BDNF mainly from the cortex. In addition, we observed a decrease in the total travel length and speed of BDNF-containing vesicles in HD neurons, indicating altered transport of these vesicles in HD. Our findings suggest a potential mechanism for the vulnerability of striatal neurons in HD and offer new insights into the pathogenic mechanisms underlying the degeneration of neurons in HD.